How to re-design German fiscal policy rules after the COVID19 pandemic - Michael Hüther; Jens Südekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
The study will first outline the way in which Germany's fiscal policy was driven for several decades by a paradigm that centered on deficit control and reduced state involvement in the economy. It will assess the damage wrought by this strategy - for example, underinvestment in infrastructure and the worsening of the financial situation in many local municipalities. Afterwards, we sketch out a new framework for fiscal policy that might take the evaluation of public needs and the need for more public investment as starting points. The study will also address the response to the Corona pandemic and in what sense it reinforces the need for a new fiscal paradigm. What are the implications of such a shock for fiscal policy rules? And how should Germany and the European Union handle the enormous public debt incurred during this crisis?
Keywords: 330